(untitled) (Itinera, 2017)
This issue gathers the interventions presented on occasion of a joint conference organised by the Department of Cultural Heritage of University of Milan and the Department of Social Sciences of the University of Parma from 14-16 October 2016 concomitantly to Expo Milan Fair. The focus of the conference, which reflects in the present publication, was ‘taste and disgust’ in Aesthetics and in the arts — seen from an interdisciplinary perspective that goes beyond a strictly academic discourse and on to the investigation of its socio-cultural repercussions.